A Study On Accessibility And Inclusivity Of Emergency Preparedness At Higher Education Institution (Hei) - Aida Syahira, Sa’adon (2024)
With an emphasis on students' understanding and attitudes, this study explores the accessibility and inclusion of emergency preparation for individuals with disabilities at Higher Education Institutions (HEIs). The study is to assess students' understanding of accessibility in emergency preparedness and investigate their perspectives on endorsing inclusive emergency plans for people with impairments. The study evaluates the awareness and attitudes of 331 students out of an entire population of 2300 at a HEI using a survey with a Likert scale. This study using quantitative method. The data collection was done through open-ended questions which 1 considered as “Strongly Agree” and 5 as “Strongly Disagree”. Level of awareness and knowledge of students regarding the accessibility and inclusivity of emergency preparedness were low. Particularly for those with disabilities or those with accessibility and functional needs, this may be the consequence of inadequate education or exposure to relevant emergency response training. Attitude of respondents remain low level. If students don't see the advantages of understanding or adhering to these protocols, their preparedness and motivation to engage in the training may suffer. Relationship between knowledge and attitudes show that the correlation between them was positively significant due to the value of r.